Reproductive biology and viviparity in the teleost Clinus dorsalis. (Perciformes:Clinidae) - Cornish, Daryl A.(Daryl Archibald) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1983.